Effectiveness of a dual surface modification of metallic interconnects for application in energy conversion devices. (29th January 2022) - Mazur, Łukasz; Ignaczak, Justyna; Bik, Maciej; Molin, Sebastian; Sitarz, Maciej; Aleksander Gil,; Brylewski, Tomasz
Abstract: A dual surface modification of an SOFC metallic interconnect with a Gd2 O3 layer and an MnCo2 O4 coating was evaluated. The tested samples were oxidized for 7000 h in air at 1073 K. Oxidation products were characterized using XRD, SEM-EDS, and confocal Raman imaging, and ASR was measured. The effect of gadolinium segregation at grain boundaries in Cr2 O3 was evaluated using S/TEM-EDS. Area specific-resistance was measured and fuel cell tests investigating electrochemical performance and Cr contamination of electrodes were also performed. The results show that the proposed dual modification was more advantageous than either modification applied separately. The fuel cell tests performed after aging in humidified hydrogen at 1073 K and involving an actual interconnect made of this dual-modified material showed that after 250 h of aging its electrochemical parameters were nearly identical to those of the non-aged reference electrode. Moreover, the modification protected the electrodes from Cr poisoning. Graphical abstract: Image 1 Highlights: Crofer 22 APU underwent single and dual modifications via dip-coating and/or EPD. Dual modification reduced the oxidation rate to a larger degree than single ones. Confocal Raman imaging allowed the phase compositions to be identified. ASR of dual-modified material after 7000 h of oxidation was excellent. Dual modification effectively protected electrode materials from Cr poisoning.